2013
DOI: 10.1016/j.pbiomolbio.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Computing life: Add logos to biology and bios to physics

Abstract: a b s t r a c tThis paper discusses the interrelations between physics and biology. Particularly, we analyse the approaches for reconstructing the emergent properties of physical or biological systems. We propose approaches to scale emergence according to the degree of state-dependency of the system's component properties. Since the component properties of biological systems are state-dependent to a high extent, biological emergence should be considered as very strong emergence e i.e. its reconstruction would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Metabolic control analysis has shown experimentally that control in intracellular networks tends to be distributed (536), that some of the key proteins and genes in E. coli failed to exercise control of the growth rate (161,398), and that such control may be distributed even among various levels in an intracellular hierarchy (537), and a combined experimental and modeling approach showed that all of this also seems to apply to ammonium assimilation (44,161). Living organisms are irreducibly (though not infinitely) complex (538,539); their analysis should be made as simple as possible but not simpler.…”
Section: The Metabolic Nitrogen State Of Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic control analysis has shown experimentally that control in intracellular networks tends to be distributed (536), that some of the key proteins and genes in E. coli failed to exercise control of the growth rate (161,398), and that such control may be distributed even among various levels in an intracellular hierarchy (537), and a combined experimental and modeling approach showed that all of this also seems to apply to ammonium assimilation (44,161). Living organisms are irreducibly (though not infinitely) complex (538,539); their analysis should be made as simple as possible but not simpler.…”
Section: The Metabolic Nitrogen State Of Cellsmentioning
confidence: 99%
“…This picture is based mainly on in vitro knowledge gathered in biochemical experiments with purified enzymes and by simplifications, typically neglecting the smaller of two parallel activities that might well be active simultaneously, as more often, Occam's razor may be deceptive in biology (538,539): that a simple explanation at first glance looks plausible enough to be real is insufficient for living organisms with their networks of irreducible core complexity.…”
Section: Gs-gogat Activity Under Conditions Of Internal Nitrogen Suffmentioning
confidence: 99%
“…The more state-dependent information we need, the stronger the emergence is. The degree of state-dependency of the component property is determined by the presence of other components in the system affecting this property, on the flux of matter through the system and on the history of the system (Kolodkin et al, 2012a,b, 2013b). In this context, we can scale and compare the strength of emergence of intelligence for different complex adaptive systems, e.g., for microorganisms, animals or humans.…”
Section: Learning From Intelligence In the Microbial Worldmentioning
confidence: 99%
“…Feedback between the participants at several levels -with oscillations being inherent in the dynamics of this feedback in order to guarantee stability. This rule defines the "first law of system biology": Any complex biological event involves activity at many levels and the properties that emerge from this activity are not necessarily predictable (Kolodkin et al, 2012). .…”
Section: The Wandering Logic Intelligence (Wli)mentioning
confidence: 99%
“…Complementarity is ubiquitous in living systems, because it provides the physicochemical basis for modular, hierarchical ordering and replication necessary for the evolution of the chemical systems upon which life is based (Root-Bernstein & Dillon, 1997;Root-Bernstein, 2012b). Recently, (Kolodkin et al, 2012) argued for replacing the tradition of Occam's razor in science (reflecting the intention to model the system as simply as possible) with a 'law of completeness'.…”
Section: What Is Missing In Current Theoretical Biology?mentioning
confidence: 99%